Oxygen Responses and Mat Formation by Beggiatoa spp - Møller, Mogens M. (1985)
The behavioral response of single Beggiatoa sp. filaments moving on a gas-permeable membrane was studied by the combined use of microscopy and oxygen microelectrodes during controlled oscillations of oxygen tension. The bacteria reacted to increasing oxygen by reversing the direction of movement. The same step-up phobic response to oxygen was observed when a filament tip or loop glided into a stable microgradient of increasing oxygen. The response was sensitive to a change in oxygen tension of <5% of air saturation min(−1). The response time was 20 to 50 s. Frequently, only part of the filament responded, which led to the formation of sharp bends, loops, and coils. This partial response facilitated the positioning of the long filaments within the narrow O(2)-H(2)S interface. The structure of whole Beggiatoa mats on sediment surfaces varied from loose to dense in relation to shallow or steep oxygen gradients in the 0.3- to 2-mm-thick, unstirred boundary layer. In an illuminated sediment Beggiatoa spp. lived together with photosynthetic organisms and migrated vertically in accordance with light/dark variations. The combined effect of phobic responses to light and oxygen can explain this migration.